Atypical presentation of a rare cardiac anomaly in an infant of diabetic mother - Mohamed, Mossad Abdelhak Shaban; Rosternberghe, Hans; Ramli, Noraida; Ibrahim, Roshidah; Mossad, Manar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia., 2020)
Introduction: Screening for heart defects in babies is widely required. Here we present a case of neonatal asphyxia and pneumothorax. Early cardiac ECHO on the first day of life can reveal a rare congenital heart defect. Presentation: This reports an infant of a diabetic mother with oligohydramnios presented with, symmetrical IUGR at 37 weeks of gestation. She presented due to foetal distress, went for instrumental delivery, and the baby was born to find with one cord coil around the neck. Upon delivery, the baby was limp and required active resuscitation and intubation. The APGAR score was 6 and 7 at one and five minutes respectively, and the cord blood gas showed a pH of 7.27 and a BE of -7.2. Ventilator settings were on minimal sittings where the baby had stable vital signs and normalized ABG, warranting extubation to high nasal flow cannula, the baby covered by first-line antibiotics awaiting the results of septic workup. The baby tolerated HFNC for a short time before experiencing respiratory distress. CXR showed right-sided pneumothorax with normal cardiac shadow, baby was reintubated. Clinical examination did not reveal any murmurs, but bedside ECHO screening was unable to pick the tributaries of the MPA. Urgent formal ECHO showed absent right pulmonary artery. CT thorax with contrast showed an oligemic right lung compared to the left lung. With ASD, RPA anomalies, Patent left PDA from aortic isthmus to the main pulmonary. Cardiac catheterization confirmed closing PDA, a blind pouch of RPA from brachiocephalic, abnormal RPA connections, disconnected RPA, and supply of PDA. Conclusion: Even in the absence of signs of CHD on physical examination and CXR, the early cardiac screen in neonates is important. Either by cardiac screen via oxygen saturation and perfusion index or real-time ECHO can accomplish early detection, intervention, and improved prognosis.